The impact of earnings management strategies on changing the credit gradient - زينب مكي محمد البناء; شيماء هادي نعمة (Iraqi Journal for Administrative Sciences, 2024)
This study aims to determining the effect of Earnings management strategies on Credit rating changes . And this is executed by depending on Earnings management strategies Both types: the first Accruals-based earnings management (AM) and the second Real earnings management (RM) . As was expressed Credit rating through financial ratios. The study is being conducted in the Iraqi banking sector. The financial information is obtained by each bank of the study sample analyzed for this purpose and the sample consists of twelve banks. For the period from 2004 to the end of 2016.The study reached several conclusions that can be expressed briefly that there is an impact of the behavior of profit management on the changes in the credit rating of each of the Iraqi banks individually and collectively